Chinmedomics strategy for elucidating the effects and effective constituents of Danggui Buxue Decoction in treating blood deficiency syndrome - Zhang, Ye; Yang, Yu; Ren, Junling; Yan, Guangli; Yang, Le; Wu, Xiuhong; Kong, Ling; Sun, Hui; Han, Ying; Zhang, Xiwu; Wang, Xijun (Frontiers in Molecular Biosciences, 2024)
Introduction: Danggui Buxue Decoction (DBD) is a clinically proven, effective, classical traditional Chinese medicine (TCM) formula for treating blood deficiency syndrome (BDS). However, its effects and effective constituents in the treatment of BDS remain unclear, limiting precise clinical therapy and quality control. This study aimed to accurately evaluate the effects of DBD and identify its effective constituents and quality markers. Methods: BDS was induced in rats by a combined injection of acetylphenylhydrazine and cyclophosphamide, and the efficacy of DBD against BDS was evaluated based on body weight, body temperature, energy metabolism, general status, visceral indices, histopathology, biochemical markers, and metabolomics. The effects of DBD on urinary and serum biomarkers of BDS were investigated, and the associated metabolic pathways were analyzed via metabolomics. Guided by Chinmedomics, the effective constituents and quality markers of DBD were identified by analyzing the dynamic links between metabolic biomarkers and effective constituents in vivo. Results: DBD improved energy metabolism, restored peripheral blood and serum biochemical indices, and meliorated tissue damage in rats with BDS. Correlation analyses between biochemical indices and biomarkers showed that 15(S)-HPETE, LTB4, and taurine were core biomakers and that arachidonic acid, taurine, and hypotaurine metabolism were core metabolic pathways regulated by DBD. Calycosin-7-glucoside, coumarin, ferulic acid sulfate, cycloastragenol, (Z)-ligustilide+O, astragaloside IV, acetylastragaloside I, and linoleic acid were identified as effective constituents improving the hematopoietic function of the rats in the BDS model. Additionally, calycosin-7glucoside, ferulic acid, ligustilide, and astragaloside IV were identified as quality markers of DBD.The hematopoietic function of DBD was confirmed through analysis of energy metabolism, biochemical markers, histopathology, and metabolomics. Moreover, by elucidating effective constituents of DBD in BDS treatment, quality markers were confirmed using a Chinmedomics strategy. These results strengthen the quality management of DBD and will facilitate drug innovation.